2015
DOI: 10.1515/msp-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the acid properties of aluminossilicate MCM-22 material synthesized under static conditions

Abstract: The hydrothermal synthesis of MCM-22 zeolite was carried out using silica, sodium aluminate and hexamethyleneimine, under static conditions at 150°C for a period of 10 days, followed by washing with deionized water, drying overnight and calcination at 650°C. The obtained material was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The XRD analysis evidenced that MCM-22 presented a well defined MWW structure. The FT-IR spectrum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
5
0
3
Order By: Relevance
“…Table II shows permeate flow and rejection coefficient data of the present study and some data presented in the literature. The zeolite membranes produced in this study (ZMDC and ZMVPT) presented satisfactory results when compared with the results found in the literature [50][51][52][53][54][55][56][57][58][59]. The results found for the zeolite membranes MCM-22 independent of the method used, dip coating or vapor transport, were similar, evidencing that the production method had no influence on the results.…”
Section: Separation Of Oil/water Emulsion Evaluation Of Ceramic and supporting
confidence: 74%
See 1 more Smart Citation
“…Table II shows permeate flow and rejection coefficient data of the present study and some data presented in the literature. The zeolite membranes produced in this study (ZMDC and ZMVPT) presented satisfactory results when compared with the results found in the literature [50][51][52][53][54][55][56][57][58][59]. The results found for the zeolite membranes MCM-22 independent of the method used, dip coating or vapor transport, were similar, evidencing that the production method had no influence on the results.…”
Section: Separation Of Oil/water Emulsion Evaluation Of Ceramic and supporting
confidence: 74%
“…This work is part of a line of research developed at the Laboratory of Development of New Materials-LABNOV of the UFCG. This line of research covered a series of studies on the synthesis of zeolite membranes in the oil/water emulsion separation process [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. This study is an integral part of this line of research and proposes the development of efficient membranes for the oil/water emulsion separation process.…”
Section: Introductionmentioning
confidence: 99%
“…A metodologia utilizada foi baseada no trabalho dos autores (Rodrigues et al, 2015). Foi preparada uma solução de hidróxido de sódio com 1,93 g dissolvidos em 415 g de água deionizada.…”
Section: Síntese Do Precursor (P)mcm-22unclassified
“…A intercalação da hexametilenoimina (HMI) entre as camadas da amostra precursora conduz ao surgimento do pico indexado (002) em 2θ = 6,56° -7,78°, comprovando a morfologia de camadas lamelares característica deste material Research, Society and Development, v. 10, n. 14, e599101422539, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i14.22539 10 (Ravishankar, et al, 2005). A formação do precursor foi então comprovada por seu difratograma de raios X apresentado na Figura 2a, o qual está em concordância com os trabalhos relatados na literatura (Lawton et al, 1996;Calgaroto et al, 2011;Carriço, et al, 2013;Elyassi, et al, 2014;Rodrigues, et al, 2015) mostrando tratar-se do precursor da zeólita MCM-22.…”
Section: (P)mcm-22unclassified
See 1 more Smart Citation